2014
DOI: 10.1111/jcmm.12376
|View full text |Cite
|
Sign up to set email alerts
|

Eye‐mediated immune tolerance to Type II collagen in arthritis‐prone strains of mice

Abstract: Type II collagen (CII) is a cartilage structural protein that plays important roles in joint function, arthritis and ageing. In studying the ability of CII to induce eye-mediated specific immune tolerance, we have recently proven that CII is capable of inducing anterior chamber-associated immune deviation (ACAID) in Balb/c mice. Here, we study the ability of CII to induce eye-mediated immune tolerance in strains of mice that are prone to the induction of rheumatoid arthritis. Thus, we hypothesized that CII ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Nowadays, other routes are under evaluation in order to develop oral tolerance strategies for immunotherapy. In this sense, eye-induced tolerance is a promising therapeutic tool in the treatment of complicated autoimmune diseases such as CIA [37,38] or EAE [3941]. Several tolerance protocols are being proposed for controlling inflammatory manifestations, in particular autoimmune diseases such as colitis [4248].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, other routes are under evaluation in order to develop oral tolerance strategies for immunotherapy. In this sense, eye-induced tolerance is a promising therapeutic tool in the treatment of complicated autoimmune diseases such as CIA [37,38] or EAE [3941]. Several tolerance protocols are being proposed for controlling inflammatory manifestations, in particular autoimmune diseases such as colitis [4248].…”
Section: Resultsmentioning
confidence: 99%
“…36 Furthermore, it has been reported that the induction of antigen-specific peripheral immune tolerance in CIA by injecting collagen type II in the immune-privileged site of the anterior eye chamber resulted in generation of Treg cells mediated via suppressive macrophages. 37 Whether such a Treg cell inducing mechanism via interaction with suppressive myeloid cells also underlies the therapeutic scheme of specific TNFR2 activation remains to be tested, for example, by the use of mice with cell-type-specific deletion of TNFR2. Thus the interaction between TNF and functionally active suppressor cells, such as MDSCs and Treg cells, seems to have a critical role in patients with chronic inflammation exerting seemingly paradoxical effects: TNF is a prototypical inflammatory mediator while, at the same time, it supports the resolution of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported that Type II collagen (CII) could induce peripheral immune tolerance via the generation of CD8 + Treg cells when CII is injected into the anterior chamber (AC) of the eye3031. Whether paroxetine and CII treatment shares common mechanisms need to be elucidated.…”
Section: Discussionmentioning
confidence: 99%